Paroxysmal oculogyric dystonia associated with a de novo 3q29 microdeletion. (August 2020) - Kaur, Harsimran; Thom, Robyn P.; Neumeyer, Ann M.; Bilancia, Colleen G.; Wray, Shirley H.; McDougle, Christopher J.
Abstract : 3q29 deletion syndrome is caused by a heterozygous 1.6 Mb deletion on chromosome 3, which occurs in about 1 in 30 000 births. Phenotypic features of this syndrome include mild-to-moderate intellectual disability, autism spectrum disorder, slightly dysmorphic facial features, ataxic gait, and chest-wall deformity. Gastrointestinal disorders, dental abnormalities, feeding problems during infancy, recurrent ear infections, and heart defects have also been observed. Since the incidence of the deletion is rare, the phenotype has not been fully described, particularly in adults. This report describes a young adult female with 3q29 deletion syndrome, autism spectrum disorder, intellectual disability, and anxiety who experienced a sustained, non-medication induced paroxysmal oculogyric dystonia which responded to anticholinergic and antihistaminic medications. This is the first report of paroxysmal oculogyric dystonia associated with this deletion, possibly expanding the phenotypic features of this microdeletion syndrome.